MELON IRRIGATION TECHNOLOGY - Mambetnazarov Esen Bisenbayevich; Bisenbayeva N.E (Galaxy International Interdisciplinary Research Journal, 2023)
Methods of irrigation of agricultural crops, irrigation water the distribution of irrigated plots and the flow pattern of water in the soil and methods and procedures used to convert to atmospheric moisture is a complex, currently above the surface of the earth (over the soil), by raining, through the soil, drip and aerosol (finely dispersed (sprinkling) irrigation is different.